A national HIV clinical mentorship program: Enabling Zambia to accelerate control of the HIV epidemic - Mary Adetinuke Boyd; Sombo Fwoloshi; Peter A. Minchella; James Simpungwe; Terence Siansalama; Danielle T. Barradas; Minesh Shah; Lloyd Mulenga; Simon Agolory (Public Library of Science (PLoS), 2022)
Although Zambia has increased the proportion of people living with HIV (PLHIV) who are on antiretroviral therapy (ART) in recent years, progress toward HIV epidemic control remains inconsistent. Some districts are still failing to meet the UNAIDS 90/90/90 targets where 90% of PLHIV should know their status, 90% of those diagnosed should be on ART, and 90% of those on ART should achieve viral load suppression (VLS) by 2020. Providing consistently excellent HIV services at all ART health facilities is critical for achieving the UNAIDS 90/90/90 targets and controlling the HIV epidemic in Zambia. Zambia Ministry of Health, in collaboration with the U.S. Centers for Disease Control and Prevention (CDC), aimed to achieve these targets through establishing a national HIV clinical mentorship program in which government-employed mentors were assigned to specific facilities with a mandate to identify and ameliorate programmatic challenges. Mentors were hired, trained and deployed to individual facilities in four provinces to mentor staff on quality HIV clinical and program management. The pre-mentorship period was July 2018-September 2018 and the post-mentorship period was July 2019-September 2019. Review of key programmatic indicators from the pre and post-deployment periods revealed the proportion of people who had a positive HIV test result out of those tested increased from 4.2% to 6.8% (P <0.001) as fewer HIV tests were needed despite the number of PLHIV being identified and placed on ART increasing from 492,613 to 521,775, and VLS increased from 84.8% to 90.1% (p <0.001). Key considerations in the establishment of an HIV clinical mentorship program include having a government-led process of regular site level data review and continuous clinical mentorship underpinned by quality improvement methodology.